Istota "planowania partnerskiego" w planach ochrony obszaru Natura 2000 - Zielińska, Anetta (The essence of "The Partnership Planning" in the projects of protected areas Natura 2000, 2006)
In “the partnership planning” the respondents of the local community and particular groups of interests are considered to be a part of the work and to be coworkers of the particular parts of the project. It creates the opportunities for better approval of the project concerning protected areas Natura 2000, as well as the social groups being interested in those areas. The key parts of "the partnership planning” process Natura 2000 are: stage of preparation, setting up the principles for the cooperation with the key groups of interests, fixing up the aims of the protection, getting up a schedule of the work, projecting monitoring process concerning the nature and getting back received information, approval of the plan.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 179-187